1982
DOI: 10.1080/03067318208078316
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Column Gas Chromatography of Environmental Polycyclic Aromatic Compounds

Abstract: The methodologies are described for isolating clean fractions of polycyclic aromatic compounds from diverse environmental samples such as air particulate matter, sediments, and fish tissue. The common step in all procedures is the separation of the polycyclic aromatic compound fraction into well-defined chemical classes by adsorption chromatography on an alumina column. These procedures greatly facilitate the detailed characterization of the polycyclic aromatic hydrocarbons, sulfur heterocycles, and nitrogen h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…3), which also indicates that vehicle emissions were also a PAH source in the urban area. In addition, at a depth of 10-30 cm, a high proportion of fluorene was detected, which is characteristic of coal and/or its combustion products (Lee et al 1982;Radke et al 2000). In our previous study on the heterocyclic aromatic hydrocarbons in Beijing soil, we found that coal and its combustion products were primary sources in the urban soil (Zhang et al 2007).…”
Section: Source Identificationmentioning
confidence: 94%
“…3), which also indicates that vehicle emissions were also a PAH source in the urban area. In addition, at a depth of 10-30 cm, a high proportion of fluorene was detected, which is characteristic of coal and/or its combustion products (Lee et al 1982;Radke et al 2000). In our previous study on the heterocyclic aromatic hydrocarbons in Beijing soil, we found that coal and its combustion products were primary sources in the urban soil (Zhang et al 2007).…”
Section: Source Identificationmentioning
confidence: 94%
“…The ratios of FL/Pyr, IND/IND + BghiP, BaP/BghiP and BaP/BaP + CHR can be used to identify the predominant sources for PAHs since the values are quite different to various sources such as gasoline emission, diesel emission, and coal combustion, respectively (Sawicki, 1962;Lee et al, 1982;Khalili et al, 1995;Kavouras et al, 1999;Kavouras et al, 2001;Manoli et al, 2004;Chen et al, 2005;Mantis et al, 2005). In this study, the ratio FL/Pyr, IND/IND + BghiP, BaP/BghiP and BaP/BaP + CHR of the six sampling sites range from 0.94 (DL) to 1.27 (SZ), 0.48 (BC) to 0.54 (HX), 1.10 (HX) to 1.25 (BC) and 0.39 (DL) to 0.43 (DXC and BC) in heating period respectively (Table 5).…”
Section: Potential Sources Of Pahsmentioning
confidence: 99%
“…The EPA Method 3510C was adopted in the extraction of organic fractions from the water samples (Lee et al, 1982) and was employed. 100 mL of water sample was measured into a 250 mL separatory funnel, and then extracted three times with 20 mL of methylene chloride, giving ~60mL of final extracting solvent.…”
Section: 1determination Of Pbdes In Water Samplesmentioning
confidence: 99%